Perbandingan splinting kawat komposit dengan splinting fiber reinforced composite untuk stabilisasi mobilitas gigi - Albert; Purnomo, Racheliza (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: Tooth mobility is a periodontal disease accompanied by loss of periodontal ligament attachment and bone destruction. Treatment for stabilization of loose teeth is splinting. The two most commonly used materials are composite wire splinting and fiber reinforced composite splinting. However, there is a dilemma in the community regarding the selection of materials that are more effective for the immobolization of loose teeth. Objective: The purpose of this study was to compare the effectiveness between composite wire splinting and fiber reinforced composites splinting for the stabilization of loose teeth. Methods: The study was conducted using the PRISMA diagram with PubMed, Researchgate, Tripdatabase and Google Scholar databases by searching (